Activity-based protein profiling in bacteria: Applications for identification of therapeutic targets and characterization of microbial communities. (February 2020) - Keller, Laura J.; Babin, Brett M.; Lakemeyer, Markus; Bogyo, Matthew
Abstract: Activity-based protein profiling (ABPP) is a robust chemoproteomic technique that uses activity-based probes to globally measure endogenous enzymatic activity in complex proteomes. It has been utilized extensively to characterize human disease states and identify druggable targets in diverse disease conditions. ABPP has also recently found applications in microbiology. This includes using activity-based probes (ABPs) for functional studies of pathogenic bacteria as well as complex communities within a microbiome. This review will focus on recent advances in the use of ABPs to profile enzyme activity in disease models, screen for selective inhibitors of key enzymes, and develop imaging tools to better understand the host–bacterial interface.